Experimental investigation of liquid retention in a cyclone evaporator under variable gravity conditions. (25th April 2016) - Buffone, Cosimo; Grishaev, Viktor; Glushchuk, Andrey
Highlights: A cyclone evaporator in both isothermal and non-isothermal cases has been studied. For 100 ml charge the fluid never left the evaporator because of the magnetic stirrer. Vp stability in low g decreases with increase in the rotational magnetic stirrer speed. Abstract: For the first time a cyclone evaporator has been designed and tested with perfectly wetting liquids in two separate experiments on condensation, at variable gravity conditions during parabolic flights. Two liquids (FC-72 and HFE-7100), with surface tension coefficient of 12–15 mN/m, were used in the experiments. The concept of the liquid retention by the centrifugal force and the specific design of the walls were validated in the first series of experiments in isothermal conditions. The liquid behaviour inside the experimental cell in weightlessness is reported and discussed for the variable liquid volume (100–200 ml) inside the cell and the rotating velocity of the magnetic stirrer inside the evaporator (0–900 rpm). The data obtained during the isothermal case were used to improve the design of the evaporation cell for the non-isothermal case, tested during a second parabolic flight campaign. In this second experiment, both the power (1.8–16 W) and rotational velocity of the magnetic stirrer (0–250 rpm) were varied. For a fluid charge of 100 ml the same fluid never left the evaporator in all tests performed with rotation of the magnetic stirrer. The vapour pressure in the cell increased during microgravity period. It was found that the stabilization of vapour pressure after transition to microgravity decreases with an increase in the rotational speed of the magnetic stirrer. We conclude that the cyclone evaporator is also an ideal candidate for those systems that have to work in microgravity and rely on pool boiling, because the cyclone chops large bubbles that would otherwise occupy the whole evaporator space and reduce the heat-transfer rate.